Descriptive Epidemiology of Anorectal Malformations in Chinese Population - Christoph Heinrich Houben; Kin Wai Edwin Chan; Kit Yi Kristine Pang; Xiang-Nan Feng; Wai Cheung Jennifer Mou; Yuk Him Tam; Kim Hung Lee (EL-Med-Pub, 2017)
Over a twelve year period one hundred and five neonates (30 females) with an anorectal malformation (ARM) were studied at a tertiary referral centre in Hong Kong. A perineal fistula was the most frequent presentation of ARM in males closely followed by rectourethral fistula. Vestibular fistula was the most common anomaly amongst females. An ARM without a fistula was documented in 11 % of patients and dominated by males. Associations and syndromes were present in nearly 30 % of the group with VACTERL association and Down syndrome at the forefront. Isolated anomalies were most frequently seen in the renal tract (23 %), the CNS (20 %) and the heart (18 %). A quarter of the cohort was small for gestational age with syndromes/associations featuring in half of this subgroup. A death rate of 9.5 % was recorded, of which all except one had an underlying syndrome or association. In addition a pre-existing heart condition constituted the most significant factor affecting the mortality in 50 % of this group.